Laser-assisted direct joining of AISI304 stainless steel with polycarbonate sheets: Thermal analysis, mechanical characterization, and bonds morphology. (February 2017) - Lambiase, F.; Genna, S.
Abstract: Laser-Assisted Metal and Plastic bonding (LAMP) of AISI304 sheets with polycarbonate sheets is investigated in this work. The process was performed by means of a high power diode laser with a maximum power of 200 W. The study introduces an integrated experimental approach aimed at understanding how the main process conditions (laser power and scanning speed) influence the direct-bonds quality, dimensions and presence of defects. To this end, the bonds dimension, shear strength, formation and dimension of bubbles in the bonded region were related to the temperature measurements and process parameters. According to the achieved results, the processing window that enables a good adhesion of the two materials is relatively small; this is due the activation of the adhesion phenomena that require overcoming an energy threshold. However, excessive energy levels reduce the bonds strength due to the increase in defects (bubbles) dimension that may combine (coalescence) leading to the formation of a central tunnel where the two substrates are completely detached. Graphical abstract: Highlights: Successful joining of aluminum AISI304 and Polycarbonate sheets by means of Laser Assisted direct Joining was achieved. Morphological analysis allowed understanding the mechanism of joint formation. Thermal analysis enabled identifying the optimal processing conditions. The line energy values were correlated to the different phenomena and defects that may develop during Laser Assisted Joining.